Neurac: A new treatment method for chronic musculoskeletal pain - Gitle Kirkesola (Fysioterapeuten, 2009)
- The effect of exercise therapy on chronic musculoskeletal pain is generally low and moderate at best. In this paper a new exercise treatment method, Neurac, is described with theoretical background, development, main content, and documentation.